Dry Eye Disease: From Causes to Patient Care and Clinical Collaboration—A Narrative Review - Pasquale Aragona; Stefano Barabino; Antonio Di Zazzo; Giuseppe Giannaccare; Edoardo Villani; Francesco Aiello; Elena Antoniazzi; Stefano Bonini; Emilia Cantera; Gianpaolo Carlini; Chiara Chierego; Rossella Colabelli; et al. (Ophthalmology and Therapy)
Abstract Dry eye disease (DED) is a common condition of the ocular surface that affects tens of millions of people worldwide. It is often characterized by decreased tear production or increased evaporation, resulting in a wide range of signs and symptoms. This review provides a comprehensive analysis of the literature related to DED, detailing causes, diagnostic tests, and medical management. Several mechanisms contribute to the maintenance of the physiological integrity of the ocular surface, and their dysfunction may result in noticeable symptoms. Accurate diagnosis is therefore essential, even when physiological function is only minimally impaired or no clear pathological signs are present. The review emphasizes the importance of addressing the underlying causes through a combination of treatment options, lifestyle changes, and enhanced communication between patients and healthcare providers to break the cycle of inflammation and tear instability. It aims to raise awareness among patients, healthcare professionals, and researchers regarding the diagnosis and treatment of DED, while also highlighting recent advancements and future challenges in its management.